Arboviruses emerging in Peru: Need for early detection of febrile syndrome during El Niño episodes - Tantaléan-Yépez, Derek (2016)
The presence of El Niño Southern Oscillation (ENSO) implies the presence of fluctuating rains in coastal areas and these changes influence the occurrence of febrile syndromes outbreaks. In Peru, Aedes aegypti is the vector responsible for various viruses such as the dengue, Zika,chikungunya, which is distributed in 18 Peruvian departments. These viruses cause similar clinical characteristics in the host and for this reason rapid, sensitive and specific diagnostic tests are needed so that the patient can receive timely treatment.